STRATEGI MITIGASI BENCANA TANAH LONGSOR DI KABUPATEN PURWOREJO - Dumilah Pradapaning Puri; Thalita Rifda Khaerani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Landslides occur in areas that exist in Indonesia, one in Central Java province. Purworejo Regency is a regency in Central Java province frequent landslides. In order to deal with the problem of landslides in Purworejo, Regional Disaster Management Agency (BPBD) Purworejo perform various disaster relief efforts including mitigation efforts. The focus and goal of this study is to formulate mitigation strategies landslides. Using the method of SWOT analysis (Strength, Weakness, Opportunities, Threats) analysis of existing strategic environment in disaster mitigation efforts landslides. This study uses qualitative descriptive type with collecting data through interviews, literature, and study the document. Informants were taken by investigators is BPBDs Purworejo. The results obtained that disaster mitigation land by BPBDs Purworejo not maximized. In practice there is no contingency plan documents landslides are used as a reference for action. The quality and quantity of human resources were inadequate. In addition, the low public knowledge and attitudes of society are apathetic towards mitigation efforts landslides hamper the implementation of mitigation efforts landslides in Purworejo. By analyzing the internal and external environment are obtained strategies are then tested using a litmus test to measure the level kestrategisan existing program based on the scores. Based on these results, it is suggested that the strategic programs that have been formulated can be implemented and applied consistently by BPBDs Purworejo. This is done to improvements in the implementation of disaster mitigation efforts landslides in Purworejo.